(untitled) (The Review of Diabetic Studies, 2025)
Sterilization remains a cornerstone of infection prevention and control within healthcare systems. This study evaluates modern sterilization practices across multidisciplinary healthcare facilities in the Kingdom of Saudi Arabia, including the pharmacy, laboratory, and physical therapy sectors, and their collective impact on healthcare-associated infection (HAI) control. Using a cross-sectional analytical framework, the research investigates sterilization standards, procedures, and levels of compliance within different healthcare disciplines. The findings indicate that variations in sterilization quality and validation processes significantly influence infection control outcomes. Centralized sterilization systems—when present—enhance consistency, traceability, and adherence to Saudi Food and Drug Authority (SFDA) and World Health Organization (WHO) guidelines. Conversely, resource constraints, limited training, and inconsistent audit mechanisms were identified as major barriers to achieving optimal sterilization standards. By highlighting the disparities and interrelations among pharmacy, laboratory, and physical therapy sterilization protocols, this study underscores the necessity of unified national policies and evidence-based quality assurance systems. Strengthening sterilization infrastructure and workforce competencies across all disciplines will be essential for advancing patient safety and reducing HAIs within the Saudi healthcare sector.